Differences in Bullying Behavior of Students from Functional and Dysfunctional Families - Dina Aprilia; Neviyarni Neviyarni (Universitas Negeri Padang, 2020)
Bullying in psychological or physical repetitive bullying of a strong person and a group of people. Bullying behavior is influenced by several factors, one of which is family functioning. This study aims to see a picture of the bullying behavior of students from functional families, the bullying behavior of students from dysfunctional families, and to examine differences in bullying behavior of students from functional and dysfunctional families. This type of research in comparative descriptive using quantitaive methods. The study population was 278 students with a sample size of 50 students, using a purposive sampling technique. Research findings reveal that, (1) the bullying behavior of students from functional families is generally in the low category, (2) bullying behavior of students from dysfuctional families is generally in the high category, (3) there are differences in bullying behavior of student from functional families and dysfunctional families, (4) the implications of the bullying behavior of students from functional and dysfunctional families.